The Importance of Critical Thinking to the Process of Acquiring Fluent English Language Skills: Enhancing Language Learning Through Critical Thinking (Journal of Advances and Scholarly Researches in Allied Education, 2022)
In order to raise people's levels of knowledge in India , critical thinking has been activelypushed on a big scale. This is because the activities that take place in the classroom do not provide pupilsthe opportunity to put their abilities in critical thinking to use. Some modern educators still favour thetime-honored, more conventional approach to instructing, in which case the pupils may not be given theopportunity to think critically. As a consequence of this, teaching critical thinking in schools wouldresult in people who are both more creative and better equipped to put their abilities to use in the future.The purpose of this study is to explore the use of critical thinking in language learning and how itcontributes to the development of English language skills among ESL students. We adopted a qualitativeapproach, and a semistructured interview format was used to acquire the necessary data. In order to geta comprehensive understanding of the ways in which students might improve their critical thinking whilestudying English, the sample consisted of thirty postgraduate students from the state of Selangor. Aqualitative method known as content analysis was utilised to assess the data. The outcomes of the studyshowed that students were able to learn more effectively when they engaged in critical thinking, whichresulted in an improvement in their command of the English language. In conclusion, the findingsdemonstrated that the students were able to engage in self-reflection and independent thought in orderto find solutions to challenges that arose in the context of their educational pursuits through the use ofcritical thinking.